MET gene amplification is a mechanism of resistance to entrectinib in ROS1+ NSCLC. Issue 21 (13th September 2022) - Tyler, Logan C.; Le, Anh T.; Chen, Nan; Nijmeh, Hala; Bao, Liming; Wilson, Timothy R.; Chen, David; Simmons, Brian; Turner, Kristen M.; Perusse, Dean; Kasibhatla, Shailaja; Christiansen, Jason; et al.
Abstract: Background: ROS1 tyrosine kinase inhibitors (TKIs) have demonstrated significant clinical benefit for ROS1+ NSCLC patients. However, TKI resistance inevitably develops through ROS1 kinase domain (KD) modification or another kinase driving bypass signaling. While multiple TKIs have been designed to target ROS1 KD mutations, less is known about bypass signaling in TKI‐resistant ROS1+ lung cancers. Methods: Utilizing a primary, patient‐derived TPM3‐ROS1 cell line (CUTO28), we derived an entrectinib‐resistant line (CUTO28‐ER). We evaluated proliferation and signaling responses to TKIs, and utilized RNA sequencing, whole exome sequencing, and fluorescence in situ hybridization to detect transcriptional, mutational, and copy number alterations, respectively. We substantiated in vitro findings using a CD74‐ROS1 NSCLC patient's tumor samples. Last, we analyzed circulating tumor DNA (ctDNA) from ROS1+ NSCLC patients in the STARTRK‐2 entrectinib trial to determine the prevalence of MET amplification. Results: CUTO28‐ER cells did not exhibit ROS1 KD mutations. MET TKIs inhibited proliferation and downstream signaling and MET transcription was elevated in CUTO28‐ER cells. CUTO28‐ER cells displayed extrachromosomal (ecDNA) MET amplification without MET activating mutations, exon 14 skipping, or fusions. The CD74‐ROS1 patient samples illustrated MET amplification while receiving ROS1 TKI. Finally, two of 105 (1.9%) entrectinib‐resistant ROS1+ NSCLC STARTRK‐2 patients with ctDNA analysis at enrollment and disease progression displayed MET amplification. Conclusions: Treatment with ROS1‐selective inhibitors may lead to MET‐mediated resistance. The discovery of ecDNA MET amplification is noteworthy, as ecDNA is associated with more aggressive cancers. Following progression on ROS1‐selective inhibitors, MET gene testing and treatments targeting MET should be explored to overcome MET‐driven resistance. Abstract : Sustained inhibition of TPM3‐ROS1 with entrectinib drives pharmacological selection of tumor cells which have evolved extrachromosomal MET gene amplification. MET amplification results in increased MET transcript and protein expression, as well as aberrant MET activation. MET activation propagates downstream signaling via the PI3K/Akt and RAS/MAPK signaling pathways, driving cancer cell proliferation and survival, and thus resistance to entrectinib therapy.